PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN KECERDASAN SPIRITUAL SISWA (Penelitian di SMP Plus Ma’arif Al-Muslihuun Kecamatan Jatinagara Kabupaten Ciamis) - Rohman, Ahmad Abdur; Masturoh, Imas (Jurnal Penelitian Pendidikan Islam, 2017)
This study aims to examine the efforts of Islamic Education Teachers in Developing Spiritual Intelligence of students at Ma'arif Al-Muslihuun Junior High School. The results of the study can be summarized as follows: 1) Efforts of Islamic Education teachers in developing students' spiritual intelligence is done through exemplary teachers, involving students in worship activities, teachers taking personal approaches, teachers educating students spiritually through stories, giving gifts and penalties, The teacher holds competencies or competitions that are held every semester for individuals or groups, the teacher creates a pleasant learning atmosphere, through the habit of reading prayer, reading short letters and reading in faithful prayer before learning Islamic Education. 2) Results of Islamic Religious Education teachers in developing students' spiritual intelligence is evidenced by students' awareness to perform congregational prayers, changes in students' attitudes become more disciplined in obeying the rules, and the emergence of interest in learning and memorizing the Qur'an; 3) Islamic Education Teacher Constraints in developing students' spiritual intelligence is a heterogeneous state of students, coming from different family environments. The solution is to do an individual approach to students, so as to facilitate the delivery of motivation to students and very well.